Question #6d237

1 Answer
Nov 22, 2016

f(x) = 3x-1 is one to one, and has the inverse f^(-1)(x) = (x+1)/3

Explanation:

A function f is said to be one to one if for any x_0, x_1 in the domain of f, f(x_0) = f(x_1) implies x_0 = x_1. In other words, there is only one element in the domain of f that maps to any given element in the range of f.

We will first show that f(x) = 3x-1 has this property. Suppose x_0 and x_1 are real numbers such that f(x_0) = f(x_1). Then

3x_0-1 = 3x_1-1

=> 3x_0 = 3x_1

=> x_0 = x_1

Thus f(x) = 3x-1 is one to one.

As f(x) is one to one, it has an inverse function f^(-1)(x) where f^(-1)(f(x)) = f(f^(-1)(x)) = x.

One way of finding f^(-1) is to set y=f(x) = 3x-1, change all the x's to y's and vice versa, giving x = f(y) = 3y-1, and then solve for y. This results in an equation of the form y = f^(-1)(x).

Set x = f(y) = 3y-1

=> x+1 = 3y

=> y = (x+1)/3 = f^(-1)(x)

Notice that given f^(-1)(x) = (x+1)/3 we have f^(-1)(f(x)) = f(f^(-1)(x))=x, as desired.